2011
DOI: 10.1111/j.1365-3083.2011.02626.x
|View full text |Cite
|
Sign up to set email alerts
|

IgG Rheumatoid Factors Against the Four Human Fc‐gamma Subclasses in Early Rheumatoid Arthritis (The Swedish TIRA Project)

Abstract: Rheumatoid factor (RF), i.e. a family of autoantibodies against the Fc part of IgG, is an important seromarker of rheumatoid arthritis (RA). Traditional particle agglutination without disclosing the antibody isotype remains the predominating diagnostic method in clinical routine. Although IgG‐RF attracts pathogenic interest, its detection remains technically challenging. The present study aimed at developing a set of tests identifying IgG‐RFs directed against the four IgG subclasses. IgG‐RF against either subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…However, this uncovered false positivity caused by Fc–Fc interactions between IgG4 present in the test sera and the IgG‐Fc used as coating . Kanmert et al reported high levels of IgG‐RF directed against IgG1‐Fc and IgG2‐Fc in IgM‐RF+/IgA‐RF+/ACPA+ RA sera, with but it was also present in controls. Elson et al reported IgG‐RF reactivity against IgG1‐Fc and IgG2‐Fc in RA sera.…”
Section: Discussionmentioning
confidence: 99%
“…However, this uncovered false positivity caused by Fc–Fc interactions between IgG4 present in the test sera and the IgG‐Fc used as coating . Kanmert et al reported high levels of IgG‐RF directed against IgG1‐Fc and IgG2‐Fc in IgM‐RF+/IgA‐RF+/ACPA+ RA sera, with but it was also present in controls. Elson et al reported IgG‐RF reactivity against IgG1‐Fc and IgG2‐Fc in RA sera.…”
Section: Discussionmentioning
confidence: 99%
“…Our results regarding binding of heat-inactivated and native sera to spotted IgG subclasses showed good agreement with this data. Yet other investigators found substantial IgG3 reactivity in serum RF of IgG isotype, however only the level of IgG1 and IgG2 specific RF was elevated in RA samples compared to healthy samples [185]. As of note the serum RF and that from synovium shows significant difference in reactivity [186], to IgG3 as well, as the synovium derived monoclonal RFs were shown to bind IgG3 in an allotype dependent manner [187].…”
Section: (7)mentioning
confidence: 84%
“…This phenomenon typically occurs under inflammatory conditions, and citrullinated proteins are recognized by autoantibodies called anti-citrullinated antibodies (ACPA), the presence of which in patients' serum is considered a diagnostic marker for RA [18]. Another autoantibody used as a diagnostic marker for the disease is rheumatoid factor (RF), which recognizes the crystallizable fraction (Fc) of immunoglobulins (Ig) G [19]. Both ACPA and RF are present in the serum of patients who will develop this disease years later [20].…”
Section: Introduction 1introduction To Rheumatoid Arthritismentioning
confidence: 99%